Optimise not compromise: The importance of a multidisciplinary breast cancer patient pathway in the era of oncoplastic and reconstructive surgery. (February 2019) - Strach, Madeleine C.; Prasanna, Thiru; Kirova, Youlia M.; Alran, Severine; O'Toole, Sandra; Beith, Jane M.; Poortmans, Philip; McNeil, Catriona M.; Carroll, Susan
Graphical abstract: Abstract: Modern breast cancer care is a complex multidisciplinary undertaking in which the integrated function of multiple constituent parts is critical, and where changes to one therapeutic component may profoundly influence the delivery and outcomes of another. Oncoplastic and reconstructive breast surgery has evolved in the era of longer survival rates for women with breast cancer and aims to enhance oncological and cosmetic outcomes. However, concurrently there has been an expansion in the indications for post-mastectomy radiation therapy (Abdulkarim et al., 2011 ; Early Breast Cancer Trialists' Collaborative Group (EBCTCG), 2014;Poortmans et al., 2015 ;Wang et al., 2011 ), the recognition of several biologically distinct breast cancer subtypes (Perou et al., 2000 ;Sørlie et al., 2001, 2003 ;Cheang et al., 2008, 2009 ;Sotiriou et al., 2003 ;Millar et al., 2011 ;Blows et al., 2010 ;Schnitt, 2010 ;Haque et al., 2012 ;Dai et al., 2015 ) and the development of recommendations for prophylactic surgery for high-risk women, including BRCA-mutation carriers (James et al., 2006 ;Domchek et al., 2010 ). Primary systemic therapy is increasingly utilised yet has varying efficacy depending on tumour biology (Cortazar et al., 2014 ). In this paper we review the evidence which informs the multidisciplinary team opinion in the era of oncoplastic and reconstructive breast surgery. We aim to describe an optimal multidisciplinary approach which balances competing risks of multimodal therapies to optimise oncological and cosmetic outcomes.